Breast Metaplastic Carcinoma With Osteosarcomatous Differentiation: A Case Report and literature Review - Xue Yang; Ling Chen; Yan Shen (SAGE Publishing, 2022)
Metaplastic breast carcinoma (MBCs) is a rare heterogeneous group of malignancies. Herein, we report a case of metaplastic breast carcinoma, which had 2 components. One of them was typical invasive ductal carcinoma (IDC), the other one was presenting as osteosarcoma with lots of immature trabeculae. The results of immunohistochemistry showed different presentations between them. The majority of MBCs show triple-negativity for ER, PR, and HER-2 and are thus associated with poor prognosis. Our report shows that, it is necessary to describe the proportion of the components and the presentations of immunohistochemistry in the diagnosis, which will be important to develop specific and effective therapies.